2020
DOI: 10.1177/0733464820967594
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease Screening Tools for Asian Americans: A Scoping Review

Abstract: With growing numbers of aging Asian Americans, Native Hawaiians, and Pacific Islanders (AANHPIs), the availability of culturally and linguistically appropriate screening tools for Alzheimer’s disease and its related dementias (ADRD) is needed. The aim of this scoping review is to summarize the tools that have been adapted for and validated among the AANHPI population. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol for systematic reviews, six databases were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Efforts to establish a strategic agenda for our Healthy Aging research track began with a systematic scoping review to map out the current state of knowledge of peer‐reviewed, interdisciplinary published literature on AD/ADRD in AAs and NH/PIs. The process and findings of the scoping review are detailed elsewhere (Lim et al, 2021). In brief, the scoping review found that AA and NH/PI older adults are underserved and underdiagnosed and there is a tremendous need for disaggregated data to understand nationally and regionally AD/ADRD prevalence, attitudes and knowledge, particularly among certain Asian subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to establish a strategic agenda for our Healthy Aging research track began with a systematic scoping review to map out the current state of knowledge of peer‐reviewed, interdisciplinary published literature on AD/ADRD in AAs and NH/PIs. The process and findings of the scoping review are detailed elsewhere (Lim et al, 2021). In brief, the scoping review found that AA and NH/PI older adults are underserved and underdiagnosed and there is a tremendous need for disaggregated data to understand nationally and regionally AD/ADRD prevalence, attitudes and knowledge, particularly among certain Asian subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…ADRD screening behavior in diverse populations may also be influenced by other sociodemographic factors including educational level, healthcare access, and relationships with healthcare professionals [ 26 , 32 , 33 , 35 , 40 , 42 , 47 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. These factors might moderate the relationship between race/ethnicity and ADRD screening seeking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…These factors might moderate the relationship between race/ethnicity and ADRD screening seeking behavior. For example, differences in educational attainment may account for the race-specific variability in screening seeking behavior [ 26 , 33 , 40 ]. Despite near-universal healthcare coverage through Medicare for seniors in the U.S, there are consistent reports of financial barriers to healthcare access, especially among racial/ethnic minority elders in the U.S. compared to Canada and other European countries [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations